EFL Teachers' Self-Efficacy in Technology Integration: A Case Study on TPACK Implementation in Schools in Indonesia - Relly Prihatin; Jovita Ridhani (FASHLUNA, 2025)
This study aims to explore English teachers' self-efficacy in integrating technology in the classroom as well as the application of the TPACK (Technological Pedagogical Content Knowledge) framework. The study also sought the relationship between teachers' self-efficacy and TPACK application when using technology in teaching. The research subjects consisted of 50 English teachers, with three teachers selected for classroom observations and retrospective interviews. Results showed that the majority of teachers had high self-efficacy in using technology such as PowerPoint, videos, and online platforms. However, some still lacked confidence in providing digital feedback. TPACK implementation varied; two teachers optimally applied it by integrating content, pedagogy and technology for interactive learning, while one teacher was passive. There is a positive relationship between teacher self-efficacy and successful TPACK implementation. Teachers with high self-efficacy were more proactive in designing innovative learning. These findings provide important implications for teacher training and education policy. Increasing self-efficacy through technology training can improve the quality of technology-based learning. Abstrak Penelitian ini bertujuan untuk mengeksplorasi efikasi diri guru Bahasa Inggris dalam mengintegrasikan teknologi di kelas serta penerapan kerangka TPACK (Technological Pedagogical Content Knowledge). Penelitian ini juga mencari hubungan antara efikasi diri guru dan penerapan TPACK saat menggunakan teknologi dalam pengajaran. Subjek penelitian terdiri dari 50 guru Bahasa Inggris, dengan tiga guru dipilih untuk observasi kelas dan wawancara retrospektif. Hasil menunjukkan bahwa mayoritas guru memiliki efikasi diri tinggi dalam menggunakan teknologi seperti PowerPoint, video, dan platform online. Namun, beberapa masih kurang percaya diri dalam memberikan umpan balik digital. Penerapan TPACK bervariasi; dua guru menerapkannya secara optimal dengan memadukan konten, pedagogi, dan teknologi untuk pembelajaran interaktif, sedangkan satu guru masih bersifat pasif. Terdapat hubungan positif antara efikasi diri guru dan keberhasilan penerapan TPACK. Guru dengan keyakinan tinggi lebih proaktif dalam merancang pembelajaran inovatif. Temuan ini memberikan implikasi penting bagi pelatihan guru dan kebijakan pendidikan. Peningkatan efikasi diri melalui pelatihan teknologi dapat meningkatkan mutu pembelajaran berbasis teknologi.